1970
DOI: 10.13057/biodiv/d140201
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity among fourteen different Fusarium species using RAPD marker

Abstract: We report genetic diversity of total fourteen different Fusarium species by RAPD-PCR analysis using 25 random primers. The genus Fusarium is food borne pathogen responsible for T-2 toxin production which affects human and animal health. In the present study, total 14-different species of Fusarium were analyzed on the basis of genetic diversity using RAPD method. A dendrogram was developed by UPGMA method. RAPD analysis was carried out by using 25 different universal primers each of them consisted of 10 bases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…Thirteen different Fusarium isolates were subjected to RAPD-PCR (Table 1). Extracted DNA was amplified by 4 selective primers (Bonde et al 2013) (Table2). PCR conditions were: an initial denaturation step at 94°C for 2 min, 35 cycles of 94°C for 30 s, 40°C for 60 s, 72°C for 2 min and a final extension at 72°C for 5 min.…”
Section: Rapd Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Thirteen different Fusarium isolates were subjected to RAPD-PCR (Table 1). Extracted DNA was amplified by 4 selective primers (Bonde et al 2013) (Table2). PCR conditions were: an initial denaturation step at 94°C for 2 min, 35 cycles of 94°C for 30 s, 40°C for 60 s, 72°C for 2 min and a final extension at 72°C for 5 min.…”
Section: Rapd Analysismentioning
confidence: 99%
“…Genetic polymorphism between isolates of F. solani was studied by Gupta et al (2009) in India by RAPD. Smith et al (2001), Arif et al (2011), Niessen (2007), Gupta et al (2009), and Bonde et al (2013) reported genetic variation among Fusarium isolates by RAPD marker.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Fusarium mycotoxin such as fumonisin has adverse health effects on animals and human hence RAPD-PCR based genetic polymorphism assay was carried out among the 28 Fusarium isolates which were isolated from popular rice varieties of India. Bonde et al (2013) obtained 180 polymorphic RAPD loci (amplified fragments were ranged 1 kb to 3.0 kb) in 14 mycotoxic Fusarium species with 25 primers and suggested RAPD marker to be a powerful tool to analyze the genetic variation among the Fusarium species. Similarly Sharma et al (2006) and Belabid et al (2004) amplified 134 and 8 polymorphic markers with 10 and 6 primers respectively.…”
Section: Genetic Variability Of Fusarium Isolatesmentioning
confidence: 99%
“…Many workers have extensively studied PCR Based genetic variability or polymorphism. The Randomly Amplified Polymorphic DNA (RAPD) assay in which DNA segments are amplified by arbitrary primers, has been used for genetic characterisation of Fusarium species and other mycotoxigenic fungi (Nelson et al, 1997;Mostafa et al, 2002;Belabid et al, 2004;Sharma et al, 2006;Lourenço et al, 2007;Gupta et al, 2009;Mishra et al, 2010;Mohammadian et al, 2011;Gupta, 2012;Bahmani et al, 2012;Bonde et al, 2013;Ebadi et al, 2013). RAPD-genetic characterisation of Fusarium species from animal feed have already been carried out based on fumonisin production.…”
mentioning
confidence: 99%